Intestinal uptake and toxicity evaluation of acetazolamide and its multicomponent complexes with Hidroxypropyl-β-Cyclodextrin in rats - Mora, Maria Julia (2015)
Large oral doses of ACZ lower the intraocular pressure (IOP), but usually lead to a multitude of systemic side effects, including gastrointestinal upset. The present study was undertaken to evaluate the effect of ACZ on the histological structure of rat duodenal mucosa and to assess a possible protective role of the complex formation of ACZ with HP-β-CD, either separately or in combination with a third compound, on the gut epithelial layer by histological and ultrastructural examinations of sections of rat duodenum exposed to ACZ or its formulations. In addition, the transport process of ACZ and its binary or ternary complexes across the duodenal mucosa by means of the single-pass intestinal perfusion (SPIP) method in rats was evaluated. Evidence was found that ACZ alters intestinal permeability and induces damage to the rat small intestine. In contrast, ACZ-induced intestinal injury may be abrogated by ACZ complexation. In addition, the complexation of ACZ with HP-β-CD, alone or in combination with a third compound, facilitated significant levels of ACZ uptake across the rat duodenal segment. Ternary complexes of ACZ with HP-β-CD in combination with TEA (triethanolamine) or calcium ions were found to provide an excellent approach that enabled an increased apparent permeability of ACZ across the duodenal epithelium, with a concomitant ability to preserve the integrity of the gut epithelium from ACZ-induced injury. These results could be useful for the design and development of novel ACZ formulations that can reduce GI toxicity, while still maintaining their essential therapeutic efficacies.